Legal Protection of Consumers in Sales and Purchase Transactions Through E-Commerce - Akhirudin; Silalahi, Wilma (Journal of Business, Management, and Social Studies, 2025)
This study aims to examine the legal protection available to consumers in e-commerce transactions and to analyze the legal responsibilities of parties involved in such digital trade interactions. The research uses a normative juridical method by analyzing legal theories, concepts, principles, and relevant statutory regulations, particularly those relating to electronic transactions and consumer protection law. The study concludes that consumer protection in e-commerce has been formally regulated under Law Number 11 of 2008 concerning Electronic Information and Transactions. This law provides specific provisions for safeguarding consumers from fraudulent digital trade practices. In cases of loss, consumers can seek redress through the Consumer Dispute Resolution Agency (BPSK) or the court. Business actors violating these provisions may face cumulative criminal sanctions, including imprisonment, fines, and administrative penalties. This paper highlights the significance of legal certainty and enforcement mechanisms in protecting digital consumers. It reinforces the relevance of adapting traditional legal protections to modern digital commerce environments, and emphasizes the state’s role in balancing business innovation with consumer rights in the digital economy.